Inequality of opportunity in health: evidence from Chile - Kevin Gallardo; Liseth Varas; Mauricio Gallardo (Universidade de São Paulo, 2017)
ABSTRACT OBJECTIVE To assess the possible presence of inequality of opportunities in the health status of Chileans, according to sociodemographic circumstances. METHODS Self-rated health data were used from the Chilean National Health Survey of 2010 to test the hypothesis of strong and weak equality of opportunities in the health status of the Chilean population. These hypotheses were tested using nonparametric techniques and second-order stochastic dominance criteria. RESULTS Robust empirical evidence was obtained, which indicate that the education level of the mother, household socioeconomic status, sex, zone, and region of residence determine opportunities to achieve good health in Chile. CONCLUSIONS Better health status was identified for Chilean adults whenever their mothers had a higher education level, their household income was higher, they were men, or lived in urban areas. The region of residence also affects opportunities to achieve good health in Chile.